Bioactivity of Sweet Flag (Acorus calamus Linnaeus) Essential Oils against Spodoptera litura Fabricius (Lepidoptera: Noctuidae) - Dewi Melani; Toto Himawan; Aminudin Afandhi (Journal of Tropical Life Science, 2016)
The study aims to determine the chemical compounds, toxicity, and antifeedant activity of sweet flag (Acorus calamus) essential oils against third instar larvae of Spodoptera litura. The study was conducted using a com-pletely randomized design (CRD) using various concentration of the essential oils (103, 2 × 103, 3 × 103, 4 × 103, 5 × 103 ppm). Mortality and antifeedant activity was observed 24 hours after treatment.  Toxicity and anti-feedant activity values were 92.5% and 79.3%, respectively, with an LC50 value 586.96 ppm. Gas chromatog-raphy-mass spectrometry analysis showed that essential oil of A. calamus consists of five chemical compounds: methyl isoeugenol, 3.9-decadien-ol-1,3-methyl-6-(1-methylethenyl), 4-pentyl-1-(4propylcyclohexyl)1cyclohexene, γ-asarone and β asarone. Keywords:  Acorus calamus, essential oils, mortality,  antifeedant,  Spodoptera lituraThe study aims to determine the chemical compounds, toxicity, and antifeedant activity of sweet flag (Acorus calamus) essential oils against third instar larvae of Spodoptera litura. The study was conducted using a completely randomized design (CRD) using various concentration of the essential oils (103, 2 × 103, 3 × 103, 4 × 103, 5 × 103 ppm). Mortality and antifeedant activity was observed 24 hours after treatment.  Toxicity and antifeedant activity values were 92.5% and 79.3%, respectively, with an LC50 value 586.96 ppm. Gas chromatography-mass spectrometry analysis showed that essential oil of A. calamus consists of five chemical compounds: methyl isoeugenol, 3.9-decadien-ol-1,3-methyl-6-(1-methylethenyl), 4-pentyl-1-(4propylcyclohexyl)1cyclohexene, γ-asarone and β asarone.